2007
DOI: 10.1007/s11738-006-0017-y
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced expression of cucumber chitinase and Nicotiana plumbaginifolia β-1,3-glucanase genes in transgenic potato plants

Abstract: The genes encoding for a cucumber class III chitinase and Nicotiana plumbaginifolia class I glucanase were co-introduced into Slovak potato (Solanum tuberosum L.) cultivar ETA using Agrobacterium tumefaciens. Expression of both genes was driven by wound-inducible polyubiquitin promoter isolated from Slovak potato breeding line 116/86. Analyses showed inducible, peel-specific expression of both transgenes under stress conditions. The effect of transgene expression on fungal susceptibility of transformants was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 40 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…In the present study, chitinase (OS03G0679700 and OS06G0726200) were increased by Cd treatment. Previous studies reported that chitinases are considered to act primarily during pathogen attack by hydrolyzing microbial cell walls 24,25 . Apparently, they might provide advantages for plants during heavy metal stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, chitinase (OS03G0679700 and OS06G0726200) were increased by Cd treatment. Previous studies reported that chitinases are considered to act primarily during pathogen attack by hydrolyzing microbial cell walls 24,25 . Apparently, they might provide advantages for plants during heavy metal stress.…”
Section: Discussionmentioning
confidence: 99%
“…The plates were incubated at 24°C for 36 h and spore germination was evaluated by measuring the OD 595 value. The turbidimetric values were normalized to the mean turbidity of the control (only buffer) and the effects of different extracts on spore germination were estimated as described by Moravcikova et al (2007).…”
Section: Chitinase Activity Assaymentioning
confidence: 99%
“…The data presented are means of three independent experiments each with five replications (standard errors of the means are not shown) a One unit of chitinase activity was defined as the amount of enzyme, which liberates 1 lmol of GlcNAc per min at pH 6.5 and 37°C. Total activity was calculated using 0.4 mg protein extract b Specific activity was expressed as units per milligram of total extracted proteins c Increased chitinase activity over the non-transgenic control d Percentage of total soluble protein e Inhibitory activity of protein extracts on spore germination was estimated using turbidimetric value (595 nm) of each sample according to the method described by Moravcikova et al (2007) Chitinase activity of the recombinant proteins Chitinase activity assays revealed that, compared to untransformed control plants, both ChiS and GH18 transgenic lines experienced up to 23-fold increases in chitinolytic activity (Table 1). Low chitinase activities in the protein extracts from non-transformed control plants (Table 1) might be attributed to endogenous chitinases.…”
Section: Molecular Analysis Of Transgenic Plantsmentioning
confidence: 99%
“…The orthologues from tomato, soybean, and tobacco enhanced defence in transgenic mustard, banana, and rice to Alternaria brassicae , Fusarium oxysporum, and Rhizoctonia solani , respectively [ 21 , 22 , 23 ]. Also, other studies have reported the positive role of transgenic β-1,3-glucanases in resistance against phytopathogens [ 24 , 25 , 26 , 27 , 28 ]. However, prospecting of other genes across a spectrum of organisms is still justified, as individual β-1,3-glucanases may exhibit differences in their antimicrobial potential [ 27 ].…”
Section: Introductionmentioning
confidence: 99%